Tinjauan Yuridis terhadap Pernikahan Beda Agama oleh Warga Negara Indonesia di Luar Negeri - Paramita, Mahardina Pradnya; Mahardika, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
Interfaith marriage remains a complex legal issue in Indonesia, particularly when conducted abroad by Indonesian citizens. The Indonesian legal framework, primarily governed by Law No. 1 of 1974 on Marriage, does not explicitly recognize or regulate interfaith marriages, leading many couples to solemnize their unions overseas to circumvent domestic legal constraints. This practice raises crucial questions about the legal recognition, registration, and civil implications of such marriages within the Indonesian legal system. Despite increasing global mobility and pluralistic societies, existing scholarship largely focuses on interfaith marriage from a domestic perspective, leaving a gap in understanding transnational legal challenges. This study aims to provide a comprehensive juridical analysis of interfaith marriages involving Indonesian citizens abroad by examining their validity, registration mechanisms, and implications on citizenship, inheritance, and family status under Indonesian law. By comparing international practices and highlighting legal inconsistencies, the study offers policy recommendations to enhance legal clarity and protection. The novelty lies in addressing the transnational dimension of interfaith marriages—a subject rarely explored in-depth within Indonesian legal scholarship—thus contributing to the reform of family law in a globalized context.